A new hemicellulose-based adsorbent for malachite green. Issue 4 (August 2018) - Gautam, Divya; Kumari, Sapana; Ram, Bhagat; Chauhan, Ghanshyam S.; Chauhan, Kalpana
Graphical abstract: Hemicellulose-based adsorbent exhibited good reusability efficiency when studied in multiple cycles and the total dye removed up to 16 cycles was 1293.38 g/g and the adsorbent was still active for further use. Highlights: Hemicellulose-based adsorbent was synthesized by periodate oxidation and acetylation. It exhibited high efficiency in malachite green removal from aqueous solutions. Adsorbent is reusable with high efficiency when studied in multiple cycles. Total dye removed in 16 cycles was 1293.38 g/g and adsorbent was still active for further use. Abstract: Utilization of biowaste is an interesting research area to develop new adsorbents. New hemicellulose-based materials were synthesized and further evaluated as malachite green (MG) dye adsorbents. Hemicellulose was extracted from Pinus wallichiana the needles, acetylated, oxidized and modified to carboxyl product. The well-characterized hemicellulose-based materials were applied to remove MG from wastewaters. The acetylated and dicarboxylated hemicellulosic material showed efficient dye adsorption with Langmuir adsorption capacity of 456.23 mg/g. The data was analyzed applying various kinetic and isotherm models, and experimental data closely matched pseudo-second order kinetic model and Freundlich isotherm. The adsorbent exhibited good reusability efficiency when studied up to 16 cycles and was still active for further use.